De-/rehydrogenation properties and reaction mechanisms of 4LiBH4–LiAlH4–MgF2 system. (7th September 2015) - Gu, R.; Wang, C.Y.; Liu, D.M.; Gao, C.; Li, Y.T.; Si, T.Z.
Abstract: In this paper, the 4LiBH4 –LiAlH4 –MgF2 ternary reactive system was constructed to investigate its de-/rehydrogenation properties and reaction mechanisms. It was found that the 4LiBH4 –LiAlH4 –MgF2 system starts to release hydrogen at about 100 °C and totally desorbs about 8.9 wt.% of hydrogen up to 480 °C. These dehydrogenation properties are much better than those of the 2LiBH4 –LiAlH4, 2LiBH4 –MgF2 and 4LiBH4 –LiAlH4 –MgH2 systems. Thermal dehydrogenation of the 4LiBH4 –LiAlH4 –MgF2 system proceeds mainly in three steps with MgAlB4, LiH and LiF as the desorbed products. After rehydrogenation at 400 °C under 6 MPa hydrogen pressure, about 4.9 wt.% of hydrogen can be desorbed during the second dehydrogenation process. Highlights: Thermal dehydrogenation occurs in the temperature range of 100–480 °C. 8.9 wt.% of hydrogen was desorbed via a three-step reaction. MgAlB4, LiH and LiF were finally formed upon dehydrogenation. 4.9 wt.% of hydrogen can be desorbed during the second dehydrogenation process.